Topographical variations of the strain-dependent zonal properties of tibial articular cartilage by microscopic MRI. (June 2014) - Lee, Ji Hyun; Badar, Farid; Kahn, David; Matyas, John; Qu, Xianggui; Chen, Christopher T.; Xia, Yang
Abstract The topographical variations of the zonal properties of canine articular cartilage over the medial tibia were evaluated as the function of external loading by microscopic magnetic resonance imaging (µMRI). T2 and T1 relaxation maps and GAG (glycosaminoglycan) images from a total of 70 specimens were obtained with and without the mechanical loading at 17.6 µm depth resolution. In addition, mechanical modulus and water content were measured from the tissue. For the bulk without loading, the means of T2 at magic angle (43.6 ± 8.1 ms), absolute thickness (907.6 ± 187.9 µm) and water content (63.3 ± 9.3%) on the meniscus-covered area were significantly lower than the means of T2 at magic angle (51.1 ± 8.5 ms), absolute thickness (1251.6 ± 218.4 µm) and water content (73.2 ± 5.6%) on the meniscus-uncovered area. However GAG (86.0 ± 15.3 mg/ml) on the covered area was significantly higher than GAG (70.0 ± 8.8 mg/ml) on the uncovered area. Complex relationships were found in the tissue properties as the function of external loading. The tissue parameters in the superficial zone changed more profoundly than the same properties in the radial zone. The tissue parameters in the meniscus-covered areas changed differently when comparing with the same parameters in the uncovered areas. This project confirms that the load-induced changes in the molecular distribution and structure of cartilage are both depth-dependent and topographically distributed. Such detailed knowledge of the tibial layer could improve the early detection of the subtle softening of the cartilage that will eventually lead to the clinical diseases such as osteoarthritis.